1984
DOI: 10.1007/bf00008620
|View full text |Cite
|
Sign up to set email alerts
|

Indicator bacteria in freshwater and marine molluscs

Abstract: The freshwater mussel Anodonta cygnea and four marine shellfish (mussels, Mytilus edulis; cockles, Cerastoderma edule ; clams, Mya arenaria ; Scrobicularia plana) from a total of six sites were surveyed for Escherichia coli, Clostridium perfringens, faecal streptococci, 25 and 37 ° C coliforms, 25 ° C and 37 ° C total viable numbers and fluorescent pseudomonads . The A . cygnea from an urban lake contained greater numbers of the faecal indicator bacteria than animals from a rural lake . There were also differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Several studies have shown that faecal bacteria can accumulate and persist in M. edulis (Al‐Jebouri and Trollope 1984; Trollope and Al‐salihi 1984; Doré and Lees 1995; Silverman et al. 1999; Hernroth et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that faecal bacteria can accumulate and persist in M. edulis (Al‐Jebouri and Trollope 1984; Trollope and Al‐salihi 1984; Doré and Lees 1995; Silverman et al. 1999; Hernroth et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other workers concluded almost the same fluctuation of total viable counts in Iraqi rivers [12,21]. Cold weather as well as availability of organic matter are playing major roles in survival and presence of heterotrophic bacteria [7]. Furthermore, total coliforms is considered as an indicator for long-term water pollution [1].…”
Section: Discussionmentioning
confidence: 90%
“…This situation will increase the risk of water pollution as the rainfalls will clean out all pollutants towards the rivers. This is one of the major causes of increased numbers and types of bacterial indicators in water bodies [1,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial communities associated with the zebra mussel have rarely been investigated and when studied, analysis involved whole mussel homogenate (Al-Jebouri and Trollope, 1984;Frischer et al, 2000;Selegean et al, 2001;Gu and Mitchell, 2002). Therefore, little is known about the differences in bacterial communities within the mussel's body.…”
Section: Introductionmentioning
confidence: 98%